2021
DOI: 10.1364/ol.432092
|View full text |Cite
|
Sign up to set email alerts
|

Flexible four-dimensional optical data storage enabled by single-pulse femtosecond laser irradiation in thermoplastic polyurethane

Abstract: Herein, a flexible four-dimensional optical data storage technique is demonstrated by harnessing ultrafast laser-induced fluorophores in thermoplastic polyurethane. By modulating the pulse energy of a 515 nm laser, data voxels with multilevel fluorescence signals can be generated and encoded. The readout accuracy of the encoded multilayer information remains at 92.2% after 50 bending cycles, demonstrating the feasibility of our technology for data recording based on a roll-to-roll method. The generation of flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…First, the feature size of MA color voxels can generally reach ≈500 nm (Figure 4B), enabling high display resolution and information density. Second, a single pulse with a strikingly low pulse energy of ≈30 nJ is enough to write one color voxel (Figure 4C), comparable with that for processing organic materials, [ 28 ] allowing for splitting a single high‐energy pulse into multiple pulses to create color voxel arrays with one shot. Accordingly, the printing efficiency of MA coloration is much higher than traditional approaches that rely on multipulse material modification.…”
Section: Resultsmentioning
confidence: 99%
“…First, the feature size of MA color voxels can generally reach ≈500 nm (Figure 4B), enabling high display resolution and information density. Second, a single pulse with a strikingly low pulse energy of ≈30 nJ is enough to write one color voxel (Figure 4C), comparable with that for processing organic materials, [ 28 ] allowing for splitting a single high‐energy pulse into multiple pulses to create color voxel arrays with one shot. Accordingly, the printing efficiency of MA coloration is much higher than traditional approaches that rely on multipulse material modification.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, dehydration of the PVA chain is expected to occur owing to laser-induced thermal effects. Fluorophore generation can be attributed to the introduction of nanoclusters [18], carbon quantum dots [19], and aromatic compounds [13,20]. However, the existence form of fluorophores remains to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the ease of creating highly-localized and targeted material modifications by femtosecond direct laser writing, microscale functional devices can be fabricated in situ [10,11]. In addition, in situ femtosecond-laser-induced fluorophores in transparent organic materials have enabled a growing number of applications, such as optical data storage [12,13], microfluidics [14], and patterning [15]. The stimuli-responsive properties of fluorescent materials have also been implemented for information security encryption [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, all these laser-interacted materials with fluorescence contrast are of potential to be new storage strategies for fluorescence-based ODS. In addition to methods mentioned above, experimental studies on laser-induced ablation, [87,88] two-photon absorption photo-bleaching, [89,90] laser-induced fluorophores [91] have also been employed to achieve high density ODS. For instance, Lu et al demonstrated that the pattern and thickness of MoS 2 sheets could be precisely controlled with a focused laser beam, resulting in layer-dependent band gap engineering.…”
Section: Photoinduced Ablation and Othersmentioning
confidence: 99%